Local Communities and the Mining Industry (Taylor & Francis, 2023)
This book explores the challenges and opportunities at the intersection of the global mining sector and local communities by focusing on a number of international cases drawn from various locations in Canada, the Philippines, and Scandinavia. Mining’s contribution to economic development varies greatly across countries. In some, it has been a major engine of development, but in others, disputes have erupted over land use, property rights, environmental damage, and revenue sharing. Corporate social responsibility programs are increasingly relied upon to manage company-community relations, yet conflicts persist in many settings, with significant costs for companies and communities. Exploring the many factors and drivers that characterize relationships among different actors within the sector, the volume contributes towards the development of practical wisdom, collective understanding, common sense, and prudence required for the mining sector and community partners to realize the economic potential and social and environmental responsibilities of non-renewable resource development. The book examines case studies from Canada, Scandinavia, and the Philippines, three regions amongst the world's top countries of mining operations. Drawing on their extensive experience in these regions, the contributors explore distinctive mining sectors in the Global North and South, the variation surrounding different types of extractive industries, and at different scales, and the legal processes in place to protect local communities. Key themes include corporate social responsibility, impact assessment, foreign ownership, Indigenous Peoples, gender, local insurgency, and mining disasters as well as climate change. The book identifies areas of future research and pathways to achieving stronger, respectful, and mutually beneficial relationships at the nexus of global mineral extraction and local communities.